Pengaruh Biochar Pukan Ayam terhadap Ketersediaan Hara dan Produksi Cabai Rawit di Tanah Alluvial - Urai Suci Yulies Vitri Indrawati; Abdul Mujib Alhaddad; Agus Suyanto; Tri Mulya Hartati (Vegetalika, 2025)
The latest data shows that cayenne pepper production in Indonesia has declined since 2024. According to the Statistics Indonesia (BPS) Horticultural Statistics, household consumption of cayenne pepper in 2024 fell 2.03% compared to 2023, and the downward trend is also evident in production. This is due to declining soil fertility, including alluvial soil, as well as climate conditions that affect crop yields. To overcome this, additional organic ameliorants such as biochar from chicken manure are needed, in addition to the use of inorganic fertilizers. The purpose of this study was to examine the effect of applying biochar from chicken manure on the productivity of chili peppers planted in alluvial soil. This study design was RAL, chicken manure biochar using 5 doses and repeated 5 times for a total of 25 treatment polybags. The treatments were P0 = control, still given NPK as recommended, P1 = 15 tons/ha, P2 = 30 tons/ha, P3 = 45 tons/ha, P4 = 60 tons/ha. The research parameters were pH, organic C, total N, available P, K-dd, height growth, and plant production. The results showed that the application of chicken manure biochar at a dose of 60 tons/ha (P4) significantly affected soil acidity (pH) (increased by 12.29%), organic carbon (74.34%), total nitrogen (62,06%), available phosphorus (170.95%), exchangeable potassium (842.80%), cayenne pepper plant height (270.57%), and fruit weight (204%).